C60 cation as the carrier of the λ 9577 Å and λ 9632 Å diffuse interstellar bands: further support from the VLT/X-Shooter spectra. Issue 4 (12th November 2021) - Nie, T P; Xiang, F Y; Li, Aigen
ABSTRACT: Ever since they were first detected over 100 yr ago, the mysterious diffuse interstellar bands (DIBs), a set of several hundred broad absorption features seen against distant stars in the optical and near-infrared wavelength range, largely remain unidentified. The close match, both in wavelengths and in relative strengths, recently found between the experimental absorption spectra of gas-phase buckminsterfullerene ions (C_60^+ ) and four DIBs at λ 9632 A, λ 9577 A, λ 9428 A and λ 9365 A (and, to a lesser degree, a weaker DIB at λ 9348 A ) suggests that C_60^+ is a promising carrier for these DIBs. However, arguments against the C_60^+ identification remain and are mostly concerned with the large variation in the intensity ratios of the λ 9632 A and λ 9577 A DIBs. In this work, we search for these DIBs in the X-shooter archival data of the European Southern Observatory's Very Large Telescope, and we identify the λ 9632 A, λ 9577 A, λ 9428 A and λ 9365 A DIBs in a sample of 25 stars. While the λ 9428 A and λ 9365 A DIBs are too noisy to allow any reliable analysis, the λ 9632 A and λ 9577 A DIBs are unambiguously detected and, after correcting for telluric water vapour absorption, their correlation can be used to probe their origin. To this end, we select a subsample of nine hot, O- or B0-type stars of which the stellar Mg ii contamination to the λ 9632 A DIB is negligibly small. We find that their equivalent widths, after being normalized by reddening to eliminate their common correlation with the density of interstellar clouds, exhibit a tight, positive correlation, supporting C_60^+ as the carrier of the λ 9632 A and λ 9577 A DIBs.